THE INFLUENCE OF TECHNOLOGICAL ADVANCEMENTS ON LANGUAGE ASSESSMENT METHODS (Scientific journal of the Fergana State University, 2024)
This study delves into how technological advancements are impacting methods used for assessing language skills, emphasizing the transformative role played by online platforms, artificial intelligence, and mobile applications. Through a mixed-methods research approach, the study analyzes the performance data of language learners who underwent both traditional and technology-enhanced assessments, while also qualitatively exploring educators' perceptions through interviews and surveys. The results suggest that technology-enhanced assessments provide more accurate, efficient, and tailored evaluations of language proficiency compared to traditional methods. Educators recognized advantages such as streamlined assessment processes and immediate feedback, but also highlighted challenges relating to the necessity for adequate training and resources. The study emphasizes the positive impact of digital tools on language assessment and advocates for their wider adoption to improve learning outcomes. It suggests the need for further research to explore the lasting effects of technology-enhanced language assessments on learners' language development and academic success.